Characteristic Poses in Ballet in the Case of a Retired Classical Ballerina after Bilateral THA: A Case Report and Review of Literature. (2nd June 2021) - Morio, Futoshi; Fukunishi, Shigeo; Fukui, Tomokazu; Kanto, Makoto; Amai, Kenta; Yoshiya, Shinichi; Tachibana, Toshiya
Abstract : Background . Ballet dance involves extreme range of motion (ROM) in the hip joint. This ROM can cause injuries including labral strain, tears, and subluxation episodes. Case Presentation . A 69-year-old female classical ballet dance instructor presented bilateral hip pain. The plain radiograph showed end-stage osteoarthritic change in the bilateral hip. She could neither dance nor perform daily activities. Bilateral hybrid total hip arthroplasty (THA) was performed. After surgery, she was able to demonstrate the split position on the floor as an active classical ballerina. The plain radiograph was taken in the split position, and the radiograph did not show any characteristics of impingement or subluxation of the femoral head. Conclusion . She was able to continue working as a classical ballet instructor after bilateral THA. Additionally, any characteristics of impingement or subluxation of the femoral head were not revealed in the postoperative radiograph in the split position.